Dawidowe świadectwo o Bożym przebaczeniu w Iz 55,3-5 na tle wewnętrznych rozterek judejskich wygnańców (lata 550-539 przed Chr.) - Zawadzki, Arnold (Verbum Vitae, 2015)
The article tries to describe the theology of David’s testimony in Isaiah 55:3-5 in light of its historical background, to wit the last decade of the Babylonian exile, and in relation to the internal quandary of Judean Exiles. The study undertakes an inquiry into the question of whether the eternal covenant in Isaiah 55:3-5 is the continuation of the Sinaitic Covenant, or rather does its content go beyond the Mosaic Law, creating a totally new relationship of God with Israel. The study also draws attention to the existence of a redactional addition, which shifts the weight of the original message from a revanchist Judeo-centrism toward the irenic ethno-centrism typical of the Book of Jonah.